2012
DOI: 10.1038/ng.2409
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies MVK mutations in disseminated superficial actinic porokeratosis

Abstract: Disseminated superficial actinic porokeratosis (DSAP) is an autosomal dominantly inherited epidermal keratinization disorder whose etiology remains unclear. We performed exome sequencing in one unaffected and two affected individuals from a DSAP family. The mevalonate kinase gene (MVK) emerged as the only candidate gene located in previously defined linkage regions after filtering against existing SNP databases, eight HapMap exomes and 1000 Genomes Project data and taking into consideration the functional impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
103
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 32 publications
3
103
1
7
Order By: Relevance
“…Exome sequencing becomes available and successfully used in disease gene mapping now with the rapid development of sequencing technology (Thompson et al 2012;Varela et al 2011;Wu et al 2012;Zhang et al 2012). With the expectation that exome sequencing markedly enhances the power of causal gene screening, we conducted an integrative analysis of exome sequencing and a genome-wide association study (GWAS) of grade II and III KBD.…”
Section: Introductionmentioning
confidence: 99%
“…Exome sequencing becomes available and successfully used in disease gene mapping now with the rapid development of sequencing technology (Thompson et al 2012;Varela et al 2011;Wu et al 2012;Zhang et al 2012). With the expectation that exome sequencing markedly enhances the power of causal gene screening, we conducted an integrative analysis of exome sequencing and a genome-wide association study (GWAS) of grade II and III KBD.…”
Section: Introductionmentioning
confidence: 99%
“…5 As reported, overexpression of the MVK protein promoted the differentiation of keratinocyte differentiation marker keratin 1 and involucrin proteins, 2 and the expression of MVK could protect keratinocytes from UV-Ainduced apoptosis. 2 We performed functional prediction of the novel missense mutation (c.1106C>G) with the use of SIFT (Sorting Intolerant From Tolerant) (http://sift.bii.a-star.edu.sg/, Maintained by the group of Pauline Ng at Genome Institute of Singapore, Singapore, Singapore) and PolyPhen-2 (Polymorphism Phenotyping v2) (http://genetics.bwh.harvard.edu, Developed by Harvard Medical School, Boston, Massachusetts, USA) software ( Table 1). Both of the prediction results confirmed that the effect of the novel mutation was deleterious.…”
mentioning
confidence: 97%
“…This disorder results in hyperkeratosis, and patients present with non-contagious dry itchy lesions that typically worsen with sun exposure. Thus, mevalonic acid may playa role in protecting keratinocytes from apoptosis induced by ultraviolet radiations (21).…”
Section: Pieces Of the Clinical Puzzlementioning
confidence: 99%